PRODUKSI BIOETANOL DARI LIMBAH KULIT NANAS DENGAN PROSES FERMENTASI MENGGUNAKAN MIKROORGANISME SACCHAROMYCES CEREVISIAE DALAM FERMENTOR TIPE BATCH - Nur Alifah, Desy; Oktofarizi, Irgy Rahmat; Septiana, Iriani Reka; Febriana, Ida; Yunanto, Isnandar (ALKIMIA, 2026)
Bioenergy is an energy resource produced through the processing of biomass formed through photosynthetic processes. One form of bioenergy is bioethanol. Bioethanol is ethanol created from the breakdown of sugars through a simple fermentation process with the role of yeast (Saccharomyces cerevisiae). One of the basic materials that can be utilized in bioethanol production is pineapple residue (Ananas comosus L. Merr). Its high carbohydrate and reducing sugar content makes it a prospective source for producing ethanol. The fermentation stage is an essential process in bioethanol production, namely the decomposition of carbohydrates into ethanol and CO₂ gas, which is then followed by a purification stage through evaporation and distillation processes. This research focuses on the processing of bioethanol derived from pineapple peel waste by varying the quantity of yeast (Saccharomyces cerevisiae) and varying the fermentation time on the resulting ethanol concentration. Based on the trial findings, the maximum ethanol concentration formed reached 80%. The highest yield was 10.2%, with an ethanol pH of 7, a water content of 0.793%, a density of 0.7397 g/ml, and a viscosity of 1.1432 cP.